Injury incidence and distribution in elite football - a prospective study of the Danish and the Swedish top divisions - Hägglund, M.; Walden, M.; Ekstrand, J. (Scandinavian Journal of Medicine & Science in Sports, 2005)
The Danish and Swedish male top football divisions were studied prospectively from January to June 2001. Exposure to football and injury incidence, severity and distribution were compared between the countries.